2019
DOI: 10.1002/pca.2853
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of artemisinin and scopoletin extraction from Artemisia annua with a new modern pressurised cyclic solid–liquid (PCSL) extraction technique

Abstract: Introduction Artemisia annua is a small herbaceous plant belonging to the Asteraceae family declared therapeutic by the World Health Organisation, in particular for its artemisinin content, an active ingredient at the base of most antimalarial treatments, used every year by over 300 million people. In the last years, owing to low artemisinin content, research of new ways to increase the yield of the plant matrix has led to the use of the total extract taking advantage from the synergic and stabilising effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In particular, casticin was found to be able to inhibit IkBs by blocking the phosphorylation activity of IKK and, consequently, the k-kB cascade [55]. The same mechanism could be attributed to scopoletin, a phenolic coumarin, known for its cytotoxicity towards cancer cells, anti-inflammatory activity, and anti-angiogenesis activity [56]. NF-kB is a transcription factor that is usually located in the cytoplasm of the cell and translocated to the nucleus when activated.…”
Section: Biological Activity Of Phyto-extractsmentioning
confidence: 97%
“…In particular, casticin was found to be able to inhibit IkBs by blocking the phosphorylation activity of IKK and, consequently, the k-kB cascade [55]. The same mechanism could be attributed to scopoletin, a phenolic coumarin, known for its cytotoxicity towards cancer cells, anti-inflammatory activity, and anti-angiogenesis activity [56]. NF-kB is a transcription factor that is usually located in the cytoplasm of the cell and translocated to the nucleus when activated.…”
Section: Biological Activity Of Phyto-extractsmentioning
confidence: 97%
“…Scopoletin, a phenolic coumarin derived from various medical or edible plants, possesses various medical properties and exhibits anti-inflammatory, anti-hypotensive ( Balkrishna et al, 2020 ), anti-diabetic ( Choi et al, 2017 ), and anti-aging activities ( Nam and Kim, 2015 ). Supercritical extraction and a new modern pressurized cyclic solid-liquid method are used for scopoletin extraction ( Jokić et al, 2016 ; Zarrelli et al, 2019 ). Under the inflammatory condition of EAE, DCs and antigen-presenting cells play an important role in disease occurrence, which can activate T cells after antigen presentation ( Zozulya et al, 2010 ).…”
Section: Nature Productsmentioning
confidence: 99%
“…Artemisia annua is a member of the Asteraceae family, with therapeutic properties mainly related to its content in artemisinin, a sesquiterpene lactone produced in the trichomes, which presents an endoperoxide bridge indispensable for its bioactivities [1]. Artemisinin and its derivatives are active ingredients at the basis of most antimalarial treatments [2], as well as present intriguing anticancer properties related to their capability to arrest cell growth, interfere with the cell cycle and/or activate multiple cell death pathways in cancer cells [3][4][5]. An increasing number of evidence suggests that the anticancer properties of A. annua are not exclusively related to a single active component of the plant, but rather to its whole phytochemical complex, including over 600 phytochemicals dominated by sesquiterpenoids, flavonoids, coumarins, enzymes and steroids [6], which may act synergistically [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely reported that the extraction strategies can significantly affect the potential therapeutic efficacy of obtained samples mainly due to their chemical composition [13][14][15]. In this context, an innovative technique, based on pressurized cyclic solid-liquid (PCSL) extraction, was recently demonstrated to be significantly more efficient than the traditional methodologies used to obtain mother tincture (European Pharmacopeia) in extracting phytochemicals from A. annua [2]. This technique is based on the creation of a pressure gradient, achieved through compressions and immediate decompressions of the plant tissue, which ultimately leads to the extraction of trichomes and avoiding any maceration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation